From ocean sprawl to blue-green infrastructure – A UK perspective on an issue of global significance. Issue 91 (January 2019) - Evans, Ally. J.; Firth, Louise B.; Hawkins, Stephen J.; Hall, Alice E.; Ironside, Joseph E.; Thompson, Richard C.; Moore, Pippa J.
Highlights: We present a UK perspective on progress towards uptake of blue-green infrastructure. We identify the barriers that remain. We present a strategy towards wider implementation in practice. Abstract: Artificial structures are proliferating in the marine environment, resulting in 'ocean sprawl'. In light of the potential environmental impacts of this, such as habitat loss and alteration, it is becoming increasingly important to incorporate ecologically-sensitive design into artificial marine structures. The principles of eco-engineering and green infrastructure are embedded in urban planning practice for terrestrial and freshwater development projects. In marine planning, however, eco-engineering of blue-green infrastructure remains an emerging concept. This note provides a UK perspective on the progress towards uptake of eco-engineering approaches for enhancing biodiversity on artificial marine structures. We emphasise that, despite a clear 'policy pull' to incorporate biodiversity enhancements in marine structures, a range of proof-of-concept evidence that it is possible to achieve, and strong cross-sectoral stakeholder support, there are still few examples of truly and purposefully-designed blue-green artificial structures in the UK. We discuss the barriers that remain and propose a strategy towards effective implementation. Our strategy outlines a step-wise approach to: (1) strengthening the evidence base for what enhancements can be achieved in different scenarios; (2) improving clarity on the predicted benefits and associated costs of enhancements; (3) packaging the evidence in a useful form to support planning and decision-making; and (4) encouraging implementation as routine practice. Given that ocean sprawl is a growing problem globally, the perspective presented here provides valuable insight and lessons for other nations at their various states of progress towards this same goal.